The Mediating Role of Cyberloafing in the Relationship Between Willpower and Academic Procrastination Among High School Students - Sezen Güleç; Hamide Yıldız (Uluslararası Türk Eğitim Bilimleri Dergisi, 2024)
Academic procrastination is regarded as one of the most significant phenomena in the field of learning in terms of its consequences and prevalence across various cultures. Thus, identifying the components that influence academic procrastination would contribute to both theoretical and practical knowledge in this area. In this context, the purpose of this study is to examine the mediating role of cyberloafing in the relationship between willpower and academic procrastination among high school students. A total of 489 high school students participated in the study, comprising 284 females and 205 males. Data was collected both in person and online through Google Forms. The findings indicated that Academic Procrastination Scale scores did not differ by gender or grade level but showed significant differences according to school type. According to the results, willpower had a significant negative correlation with both cyberloafing and academic procrastination, whereas cyberloafing was positively correlated with academic procrastination. Finally, the results revealed a partial mediating role of cyberloafing in the relationship between willpower and academic procrastination. The findings are discussed based on the existing literature, and recommendations are provided.